Decreased Quality of Life in Children With Anomalous Aortic Origin of a Coronary Artery. Issue 2 (March 2021) - Agrawal, Hitesh; Mery, Carlos M.; Sami, Sarah A.; Qureshi, Athar M.; Noel, Cory V.; Cutitta, Katherine; Masand, Prakash; Tejtel, S. Kristen Sexson; Wang, Yunfei; Molossi, Silvana
Background: Anomalous aortic origin of a coronary artery (AAOCA) is associated with sudden death in the young. We sought to determine quality of life (QOL) in patients/families affected by AAOCA. Methods: Patients with AAOCA (8-18 years) were prospectively included from January 2016 to May 2017. Parent proxy and patient Pediatric Cardiac Quality of Life Inventory (PCQLI) were used to evaluate QOL and Pediatric Quality of Life Inventory (PedsQL) Family Impact Module to assess the impact of AAOCA on families, as primary outcomes. Secondary outcomes included peer relationship, anxiety, and depression assessed using patient-reported outcomes measurement information system. Patients deemed high-risk were offered surgery/exercise restriction. Generalized linear mixed regression models were used to determine significant predictors of outcomes. Results: Fifty-three patients, the majority (n = 31, 59%) unrepaired, and 49 caregivers were included. Using PCQLI, patient and parent proxy QOL scores were similar to published scores for children with long-QT syndrome. Patients' QOL score was associated with exertional symptoms, perceived chronic disease, and altered parent's concentration ability. Likewise, parent proxy QOL scores were associated with mother's living situation, exertional symptoms, parent missing work for ≥1 day, and disturbed parental functioning at work. Family impact scores were associated with lower maternal education, among other measures. Risk categories or surgical status did not impact patient, parent proxy reported, or family impact QOL. Conclusion: Anomalous aortic origin of a coronary artery is associated with decreased QOL as perceived by patients and caregiver and is associated with numerous facets of family functioning. These findings are independent of risk categorization or surgical status.